Ideology Movements of Trisakti Trilogy: Remending Maritime Archipelagic as a Concept of Indonesian Unity in the Threat of Democracy and Sovereignty Crisis - Luthfi Habibullah; Bagus Haryono; Argyo Demartoto (Diponegoro University, 2022)
Indonesia has great potential in managing its maritime strength. Historical traces have recorded that Nusantara kingdoms succeeded in showing their strength to build geopolitical and global trade routes. Having a geographical structure makes Indonesia pay great attention to the sea. Archipelagic state is not merely interpreted as an archipelagic concept, but it is a state that connects islands to and from a sovereign territory by presenting a national maritime power. Indonesia is expected to be a successor to the maritime nation considered in Southeast Asia and also to play its role in the global geopolitical strategy. National unity must be followed by strong geographical entity. The emergence of the Juanda Declaration as a diplomacy order was to defend the principles of the sovereign island nation of Indonesia. The sea is no longer defined as a separator, but a link and unifying sovereignty. State sovereignty become the foundation of the Trisakti trilogy. Fully sovereign in political, self-sufficient in economic and conforming personality in cultural values are the basis of the foundation. It rejects all forms of new-style imperialism, capitalism and foreign dictation of life value system.